Inhibitory effect of isolated Lactobacillus from oral cavity against bacterial Pathogens and its effect on health promotion - Khalil Azizian; Sepehr Taghizadeh; Rasoul Hosseinpour; Asghar Tanomand; Elham Sheykhsaran; Naser Alizadeh; Behrooz Naghili; Hossein Samadi Kafil
ABSTRACT Aims: To determine the inhibitory effect of oral Lactobacillus against bacterial pathogens and investigate correlation between presence of Lactobacillus strains and health promotion. Method: One hundred saliva samples were collected from oral cavity of domestic dairy consumers and were investigated for the isolation and identification of Lactobacillus strain by conventional culture and sequencing of 16SrRNA. Furthermore, well diffusion assay was performed to determination of antibacterial activity of Lactobacillus strains against bacterial pathogens including Salmonella typhimurium, Klebsiella pneumoniae, Shigella sonnei, Shigella dysenteriae, Enterococcus faecalis and Enterococcus faecium. Finally, association between health condition and isolation of Lactobacillus were investigated and obtained data using questionary form were analysed by chi-square test. Results: Thirty Lactobacillus strains recovered from 100 hundred saliva samples. The most common isolated strain was L. gasseri (n=18) and followed by L. vaginalis (n=3) and L. salivarius (n=3). All Lactobacillus strains demonstrated antibacterial activity against at least one of the investigated pathogens. However, the strongest results were obtained by L. vaginalis against K. pneumonia. The correlation between the presence of thirty Lactobacillus strains and health promotion not found. However, only L. gasseri species has significant positive impact on health in their hosts (P < 0.05). Conclusion: Only some Lactobacillus species have a positive impact on health promotion. Despite of weak activity against the investigated pathogens, L. gasseri has a positive impact on the mental problem (intense anger and depression) of their hosts.